Removing blurring for better understanding the main challenges facing digital entrepreneurs in the digital era: An empirical investigation study from emerging country - Moh'd Anwer AL-Shboul (Heliyon, 2024)
The purpose of this study is to examine the main challenges that these entrepreneurs in developing nations confront. This study utilizes a digital startup database maintained by the Ministry of Digital Economy and Entrepreneurship (MoDEE) in Jordan and conducts semi-structured interviews with a random selection of 85 early-stage digital entrepreneurs. In order to understand the cognitive and psychological characteristics of digital entrepreneurs and their motives for entering the field, this study draws on the theory of planned behavior. Using NVivo 20, a theme analysis is carried out. Based on the interviews conducted, the top industries among the startups that were looked at were big data and business analytics, internet-of-things (IoT), cybersecurity (CT) technology, food service and agri-tech, warehouse automation (WA) and elastic logistics (ELs), conversional artificial intelligence (CAI), financial technology (FinTech), and block chain technology (BCT). 42.5 % of the target population is represented by the large sample size that was used. These obstacles could include long-term funding, a dearth of one-on-one coaching and guidance, unforeseen risks or setbacks, and financial constraints. The study's conclusions may provide policymakers with a tactical manual for removing the main barriers that emerging digital entrepreneurs and their firms must overcome.